2015
DOI: 10.3892/or.2015.4003
|View full text |Cite
|
Sign up to set email alerts
|

The histone methyltransferase EZH2 promotes mammary stem and luminal progenitor cell expansion, metastasis and inhibits estrogen receptor-positive cellular differentiation in a model of basal breast cancer

Abstract: Abstract. Mammary stem cells (MSCs) are the progenitor population for human breast epithelia. MSCs give rise during mammary gland development to estrogen receptor (ER)-negative basal cells and the ER -luminal progenitor (LP) population which maintains ER + and ER -luminal cells. The MSC population is expanded and tumorigenic in some mouse mammary cancer models, and these tumor-initiating cells have been isolated from human breast cancers. MSC expansion is associated with aggressive biological behavior in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…While we cannot totally exclude the possibility that the ability of EZH2 expression to predict breast cancer is linked to cell proliferation, we favor the previously suggested hypothesis that its role as a predictor of breast cancer may depend on its effect on stem cell survival and alteration of DNA repair pathways [24, 2630]. …”
Section: Discussionsupporting
confidence: 42%
“…While we cannot totally exclude the possibility that the ability of EZH2 expression to predict breast cancer is linked to cell proliferation, we favor the previously suggested hypothesis that its role as a predictor of breast cancer may depend on its effect on stem cell survival and alteration of DNA repair pathways [24, 2630]. …”
Section: Discussionsupporting
confidence: 42%
“…To address whether these sites correlate with transcriptional repression in accordance with the down regulation of HYAL1 by estrogen (Figure 1A and Figure 3), we performed ChIP assay for the histone H3K27me3 repressive mark. The methylation of H3K27 is catalyzed by the polycomb repressive complex 2 (PRC2) member enhancer of zeste homolog 2 (EZH2/KMT6A), which has been associated with repression of estrogen-responsive genes and with the severity and progression of breast cancer [30, 31]. We found that the ERE-900 was strongly associated with the H3K27me3 mark in presence of estrogen, in contrast to more distal sites (Figure 5C), suggesting that the ERE-900 located in the proximal promoter of HYAL1 is linked to estrogenic repression.…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer, histone hypermethylated marks are frequently associated to genes involved in cell-cycle regulation, apoptosis, tissue invasion and metastasis [33, 34]. In particular, the methyltransferase EZH2/KMT6A and its end-product H3K27me3 mark are found elevated in aggressive breast cancer subtypes, including triple negative and ERα-positive tumors resistant to endocrine therapies, suggesting inactivation of tumor suppressor genes [31, 3538]. Our results demonstrate that H3K27 methylation profile associated with the ERα binding sites identified throughout the 3p21.3 cluster is highly variable, suggesting the potential of estrogen to selectively up- or down-regulate specific genes within this cluster.…”
Section: Discussionmentioning
confidence: 99%
“…But, unlike CBX7, EZH2 overexpression was highly linked to the proliferation marker MKI67, suggesting a different role of these two proteins in breast tumorigenesis (37). Numerous studies point on the widespread roles of PRC2 (as well as H3K27 methylation) in developmental and differentiation processes of multicellular organisms, and on their implication in fundamental chromatin mechanisms that underlie stem cell regulatory circuits and cancer progression (38). Thus, it is not surprising that increasing evidences indicate that EZH2 deregulation is frequently observed in a variety of cancers (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%